A poroelastic model coupled to a fluid network with applications in lung modelling. (21st July 2015) - Berger, Lorenz; Bordas, Rafel; Burrowes, Kelly; Grau, Vicente; Tavener, Simon; Kay, David
Summary: We develop a lung ventilation model based on a continuum poroelastic representation of lung parenchyma that is strongly coupled to a pipe network representation of the airway tree. The continuous system of equations is discretized using a low‐order stabilised finite element method. The framework is applied to a realistic lung anatomical model derived from computed tomography data and an artificially generated airway tree to model the conducting airway region. Numerical simulations produce physiologically realistic solutions and demonstrate the effect of airway constriction and reduced tissue elasticity on ventilation, tissue stress and alveolar pressure distribution. The key advantage of the model is the ability to provide insight into the mutual dependence between ventilation and deformation. This is essential when studying lung diseases, such as chronic obstructive pulmonary disease and pulmonary fibrosis. Thus the model can be used to form a better understanding of integrated lung mechanics in both the healthy and diseased states. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A novel coupled poroelastic‐airway network flow model is presented. By using low‐order stabilised finite elements, a reliable and efficient computational model is constructed. Finally, by using simplified lung disease scenerios, for example, airway constriction, this model shows how such local diseases impact globally upon lung function.